Diet composition and reproductive biology of spineless cuttlefish Sepiella inermis (Orbigny, 1848) from Ratnagiri (Arabian Sea, North-west coast of India) - Mahadwala, P. L.; Nirmale, V H; Metar, S. Y.; Bhosale, B P; R. A. Pawar; Chogale, N D (Indian Journal of Fisheries, 2023)
In the present study, we investigated some biological aspects of the spineless cuttlefish,Sepiella inermis (Orbigny, 1848) along the Ratnagiri coast of Maharashtra, India. A study ondiet composition and reproductive biology of the species was carried out. Dorsal mantlelength (DML) ranged from 35.9 to 93.3 mm for males and 29.3 to 98 mm for females.Feeding intensity was noted to be low during most of the study period. S. inermis was foundto have a protracted spawning season. The overall male: female ratio was 1:1.02 during thestudy period. The average fecundity was found to be 358 eggs. Length at sexual maturitywas estimated to be 42 mm and 53 mm for males and females respectively. The informationobtained from the study will help the fishery agencies to formulate management measuresin sustaining the landings of S. inermis in the region.Keywords:Biological studies, Cephalopods, Maharashtra,Ratnagiri coast, Sepiella inermis, Spinelesscuttlefish